Analisis Kepuasan Masyarakat pada Tenaga Kesehatan di Puskesmas Muara Bangkahulu Kota Bengkulu - Aldi Al Caesar, Muhammad; Suratman, Suratman; Yogopriyatno, Jatmiko (PESIRAH: Jurnal Administrasi Publik, 2023)
Research was conducted at Muara Bangkahulu Community Health Center, Bengkulu City, to analyze community satisfaction with health workers. A descriptive qualitative approach was used in this study through observation, interview and documentation activities to conduct data collection. The study found that the services provided were generally satisfactory in terms of competence and meeting community needs, although some patients were dissatisfied with the behavior of health workers. Routine information dissemination and vaccination of under-fives were identified as supporting factors, while factors such as lack of seating, lack of medical personnel and medical equipment, and punctuality of officers were identified as inhibiting factors.